Київська спадщина у писемності Великого князівства Литовського - Прискока, О.В.; Франчук, В.Ю. (Мовознавство, 2013)
У статті йдеться про складні шляхи формування старобілорусько-української літературної мови на території Великого князівства Литовського. Незважаючи на те, що із зазначеного питання існує чимало наукової літератури, деякі аспекти цього процесу недостатньо вивчені. Зокрема, авторами здійснено лінгвістичний аналіз документів ВКЛ у зіставленні з діловою писемністю Київської Русі, уточнено на лексичному рівні місце та роль раннього літописання ВКЛ, створеного на основі давньокиївської літописної традиції (Літопис Авраамки), у формуванні старобілорусько-української літературної мови. The article deals with complex ways of creating old Belarusian -Ukrainian literary language in
the Grand Duchy of Lithuania. Despite the fact that there are a lot of scientific papers, some aspects
of this process have been insufficiently studied. In particular, the authors conduct a linguistic analysis
of the GDL documents in comparison with Kievan Rus business script, make more accurate the
place and role of early GDL chronicles, created from Ancient Kyiv literary tradition (Chronicle
Avraamky), in the formation of old Belarusian -Ukrainian literary language at the lexical level.
Some study documents showed that religious personal names are used along with the pagan
names in speech acts of GDL and mostly Christian name Prince accompanied by his pagan name that
was probably most famous: «кня/з/ велебныи Дмитрии. шгЬмъ імене/м/. корибу/т/» (1388).
It is also proved that the structure of GDL acts and its form fully preserve East Slavic tradition of
paperwork which originates from the pre-Christian era.
Lexical analysis of annalistic genre showed that Avraamky Chronicle, a chronicle collection,
created in 1495 in the GDL under the rule of the Lithuanian Grand Duke Alexander (Vytautas), has
42.4 % of terminological vocabulary fixed in Lavrentivskomu Chronicle—the most valuable source
of Ancient Kyiv day vocabulary learning . This lexicon contains lexical units of about 30 thematic
groups of words, including the names of construction and architecture, military terminology, the
names of settlements and territorial-administrative division, domestic, agricultural vocabulary,
names of monetary units, etc.
Both chronicle collections reflect quite noticeable building and architecture vocabulary layer in
ancient literature. These are names of building structures and housing: домь, хоромъ, полата, вежа,
келья, печера, шатер, кліть, гридьнща; defensive structures and their parts: градъ, ocтрогъ, дітинець, валь, заборола,ровъ, гребля, мостъ; labor processes in construction: рубити,
срубити, здати, огородити, оградити, etc.
Thus both genres: more business genre with its folk-spoken element and less extent chronicle
genre — are essential sources of old Belarusian—Ukrainian written language of GDL, a foundation
inherited from Kievan Rus.